Adaptive spectral processing algorithm for staggered signals in weather radars - Collado Rosell, Arturo (2020)
Fil: Collado Rosell, Arturo. Instituto Balseiro - Universidad Nacional de Cuyo, 2LIAT, Dto. de Ingeniería en Telecomunicaciones